2007
DOI: 10.1016/j.ejsobi.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The application of vegetable, fruit and garden waste (VFG) compost in addition to cattle slurry in a silage maize monoculture: Effects on soil fauna and yield

Abstract: In Flanders, vegetable, fruit and garden (VFG) wastes are collected selectively and composted. We studied the effects of the combined application of three different doses of VFG compost and cattle slurry during 7 years on maize dry matter yields and three soil faunal groups: nematodes, micro-arthropods (springtails and mites) and earthworms. Combined application of VFG compost and slurry resulted in the highest yields. Initially, there was a clear yield depression on plots amended with compost in contrast to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
1
45
2
1
Order By: Relevance
“…It is consistent with the results obtained in the study of Leroy et al (2007) who found clear yield depression of maize on plots amended with compost at the beginning of a 7-year experiment in contrast to an upward trend in the last application years, proving a significant residual N effect from cumulative compost application. The yield after compost II application was 2.3 times higher compared to compost I in our experiment and the difference was significant.…”
Section: Resultssupporting
confidence: 82%
“…It is consistent with the results obtained in the study of Leroy et al (2007) who found clear yield depression of maize on plots amended with compost at the beginning of a 7-year experiment in contrast to an upward trend in the last application years, proving a significant residual N effect from cumulative compost application. The yield after compost II application was 2.3 times higher compared to compost I in our experiment and the difference was significant.…”
Section: Resultssupporting
confidence: 82%
“…In a study by Sleutel et al (2006), 41 years of application of 35 t farmyard manure ha −1 , plus an equivalent amount of NPK in mineral fertilizer, every 5 years in a wheat-wheat-sugarbeet-maize-maize crop rotation, increased grain yield by 124 and 55% for maize and wheat in respect to the control. Moreover, in a 7-year study, Leroy et al (2007) investigated vegetable-fruit-garden-waste compost combined with cattle slurry applied at both 22.5 t ha −1 yearly and 45 t ha −1 every other year. Both the application strategies resulted in 25 to 43% higher maize yields in respect to the two organic amendments provided alone.…”
Section: Yield Responsementioning
confidence: 99%
“…The application of slurry (C:N=8:1) and fruit or garden waste compost (C:N=10:1) reduced the population of Pratylenchus spp. and Tylenchidae in maize monoculture (Leroy et al, 2007). Reversal, yard waste compost (leaves, branches, grass clippings) with the C:N ratio from 35:1 to 46:1 had no effect on population densities of Pratylenchus spp.…”
Section: Discussionmentioning
confidence: 99%